(1)
(2)
(3)
(4)
(5)x÷
(6)
(7)9a2b÷
(8)
(9)
(10)(-
(11)[
(12)(
|
(1)原式=
=1 (x-y)(x+y)
;1 x2-y2
(2)原式=
×a-b a(a+b) a2(b+a)(b-a) -a(a-b)
=a-b;
(3)原式=
•(x-1)(x+8) x(2-x)(2+x) (x+2)(x-2) 3(x+8)
=
;1-x 3x
(4)原式=
×(x+y)2 y(x-y) (x-y)2 y(x+y)
=
;x2-y2 y2
(5)原式=x•x•x
=x3;
(6)原式=
×x2(x+1) (1+x)(1-x)
•1 x 1 x
=
;1 1-x
(7)原式=9a2b•
•4ab24b 3a
=48a2b3;
(8)原式=
•a-4 (a+2)2
•(a+2)(a+3) (a+1)(a-2) a-2 a+3
=
;a-4 (a+2)(a+1)
(9)原式=
•x(x+y) x(x-y)
•1 x-y x(x-y) xy
=
;x+y y(x-y)
(10)原式=
•a4 b2
•b3 a3 1 a4b4
=
;1 a3b3
(11)原式=[
•(x-y)2 x+y
]3x2 -(x+y)(x-y)
=[
]3x-y -(x+y)2
=-
;(x-y)3 (x+y)6
(12)原式=[
]2•x-1 (x+1)(x-2)
•x2(x+1)22-x (x-1)2
=
•(x-1)2 (x+1)2(x-2)2
•x2(x+1)22-x (x-1)2
=
.x2 2-x